Rapid photo-degradation of various organic dyes with thin-layer boron-doped graphitic carbon nitride nano-sheets under visible light irradiation. Issue 2 (April 2020) - Zhong, Yingying; Lin, Yaohui; Chen, Qian; Sun, Ying; Fu, FengFu
Graphical abstract: Highlights: A thin-layer boron-doped g-C3 N4 nanosheet with high and stable photocatalytic activity was prepared. It can be used as photocatalyst for fast degrading various organic dyes under visible light irradiation. The possible mechanism and route of various dyes degradation were also investigated. Abstract: We herein prepared the boron-doped graphitic carbon nitride (B-g-C3 N4 ) nano-sheets with 1–5 monolayers and 50−200 nm size via heating the mixture of melamine and boron oxide. We demonstrated that the prepared thin-layer B-g-C3 N4 nano-sheets have a high and stable photo-catalytic activity for degrading various organic dyes with a high speed and efficiency under visible light irradiation. In the presence of 2 mg/mL of B-g-C3 N4 nano-sheets, Eosin Y (EY, heterocyclic dye), Rhodamine B (RhB, triarylmethane dye), Methylene blue (MB, thiazide dyes) and Methyl orange (MO, Azo dyes) can be completely degraded within 5, 10, 20 and 60 min respectively under visible light irradiation follow the first-order kinetics. The possible route and intermediate products of various dyes during photo-degradation over B-g-C3 N4 nano-sheets were also investigated. In comparison with other g-C3 N4 or g-C3 N4 -based materials, the prepared thin-layer B-g-C3 N4 nano-sheets have much higher photo-catalytic activity and can be used for visible light-driven degrading various organic dyes. The success of this study provides a promising method for economical, rapid and environmental-friendly treatment of dye-contaminated water.